Pengaruh Lingkungan Kerja, Kompensasi, dan Kepemimpinan terhadap Kepuasan Kerja pada Pegawai Bagian Keuangan PT POS Indonesia Semarang - Arisandi, Irma; Nurdhiana, Nurdhiana (STIE Widya Manggala, 2014)
The study aimed to determine the effect of work environment, compensation, and leadership on job satisfaction of employee in financial department of PT Pos Indonesia (Persero) Semarang. The population was 52 people, while the samples were non-probability sampling technique by census. This study was also conducted with the validity and reliability, an analysis tool used was multiple linear regression. The results of the study showed that work environment, compensation, and leadership had positive and significant effect on job satisfaction of employee in financial department of PT Pos Indonesia (Persero) Semarang. The magnitude of the effect of work environment, compensation, and leadership on job satisfaction of employee in financial department of PT Pos Indonesia (Persero) Semarang of 67.8 % and the remaining 32.2 % was caused by other variables outside the model